Copolymers of phenacyl methacrylate with glycidyl methacrylate: synthesis, characterization and monomer reactivity ratios - Soykan, C; Ahmedzade, M; Coskun, M (Pergamon-Elsevier Science Ltd, 2000)
Copolymers with various proportions of phenacyl methacrylate (PAMA) and glycidyl methacrylate (GMA) were prepared by free radical-polymerization in solution in 1,4-dioxane using 2,2'-azobisisobutyronitrile as initiator at 70 degrees C. The polymers were characterized by infrared and H-1 and C-13 nuclear magnetic resonance (NMR) spectroscopy. The copolymer compositions were determined by H-1-NMR spectra. The reactivity ratios were calculated by both Fineman-Ross and Kelen-Tudos methods. Glass transition and decomposition temperatures of copolymers were determined. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: phenacyl methacrylate; glycidyl methacrylate; copolymerization; characterization; reactivity ratios